The extraplanar type II supernova ASASSN-14jb in the nearby edge-on galaxy ESO 467-G051 - Meza N; Prieto JL; Clocchiatti A; Galbany L; Anderson JP; Falco E; Kochanek CS; Kuncarayakti H; Sanchez SF; Brimacombe J; Holoien TWS; Shappee BJ; et al. (EDP SCIENCES S A, 2022)
We present optical photometry and spectroscopy of the Type II supernova ASASSN-14jb, together with Very Large Telescope (VLT) Multi Unit Spectroscopic Explorer (MUSE) integral field observations of its host galaxy and a nebular-phase spectrum. This supernova, in the nearby galaxy ESO 467-G051 (z = 0.006), was discovered and followed-up by the all-sky automated survey for supernovae (ASAS-SN). We obtained well-sampled las cumbres network (LCOGTN) BVgri and Swift omega 2m1 omega 1ubv optical, near-UV/optical light curves, and several optical spectra in the early photospheric phases. The transient ASASSN-14jb exploded similar to 2 kpc above the star-forming disk of ESO 467-G051, an edge-on disk galaxy. The large projected distance from the disk of the supernova position and the non-detection of any H II region in a 1.4 kpc radius in projection are in conflict with the standard environment of core-collapse supernova progenitors and suggests the possible scenario that the progenitor received a kick in a binary interaction. We present analysis of the optical light curves and spectra, from which we derived a distance of 25 +/- 2 Mpc using state-of-the-art empirical methods for Type II SNe, physical properties of the SN explosion (Ni-56 mass, explosion energy, and ejected mass), and properties of the progenitor; namely the progenitor radius, mass, and metallicity. Our analysis yields a Ni-56 mass of 0.0210 +/- 0.0025 M-circle dot, an explosion energy of approximate to 0.25 x 10(51) ergs, and an ejected mass of approximate to 6 M-circle dot. We also constrained the progenitor radius to be R-* = 580 +/- 28 R-circle dot which seems to be consistent with the sub-Solar metallicity of 0.3 +/- 0.1 Z(circle dot) derived from the supernova Fe II lambda 5018 line. The nebular spectrum constrains strongly the progenitor mass to be in the range 10-12 M-circle dot. From the Spitzer data archive we detect ASASSN-14jb approximate to 330 days past explosion and we derived a total dust mass of 10(-4) M-circle dot from the 3.6 mu m and 4.5 mu m photometry. Using the FUV, NUV, BVgri,K-s, 3.6 mu m, and 4.5 mu m total magnitudes for the host galaxy, we fit stellar population synthesis models, which give an estimate of M-* approximate to 1 x 10(9) M-circle dot, an age of 3.2 Gyr, and a SFR approximate to 0.07 M-circle dot yr(-1). We also discuss the low oxygen abundance of the host galaxy derived from the MUSE data, having an average of 12 + log (O/H) = 8.27(-0.20)(+0.16) using the O3N2 diagnostic with strong line methods. We compared it with the supernova spectra, which is also consistent with a sub-Solar metallicity progenitor. Following recent observations of extraplanar H II regions in nearby edge-on galaxies, we derived the metallicity offset from the disk, being positive, but consistent with zero at 2 sigma, suggesting enrichment from disk outflows. We finally discuss the possible scenarios for the unusual environment for ASASSN-14jb and conclude that either the in-situ star formation or runaway scenario would imply a low-mass progenitor, agreeing with our estimate from the supernova nebular spectrum. Regardless of the true origin of ASASSN-14jb, we show that the detailed study of the environment roughly agree with the stronger constraints from the observation of the transient.